Electret states and the phase transition in a surface layer of the TiGaSe2 ferroelectric semiconductor - Seyidov, Mir-Hasan Yu.; Suleymanov, R. A.; Khamoev, R. (Pleiades Publishing Inc, 2006)
The electret polarization is investigated in the TIGaSe2 ferroelectric semiconductor. It is proved for the first time that stable internal electric fields associated with residual electret polarization are induced in crystals of the TIGaSe2 ferroelectric semiconductor at temperatures T < 200 K. It is experimentally established that the peak of the pyroelectric current measured in the vicinity of the phase transition to the ferroelectric polar phase depends substantially on the temperature at which the external electric field is switched off when the TIGaSe2 feffoelectric crystal under investigation is preliminarily cooled from room temperature. The results obtained are discussed in the framework of a model according to which internal electret fields are induced by charges localized at different levels in the bulk and on the surface of the TlGaSe2 ferroelectric crystal. These fields drastically change at temperatures in a narrow range near 135 K. The inference is made that a phase transition occurs in the surface layer of the TlGaSe2 crystal at a temperature close to similar to 135 K.